Cost of neonatal abstinence syndrome: an economic analysis of English national data held in the National Neonatal Research Database. Issue 5 (24th February 2021) - Rees, Philippa; Carter, Ben; Gale, Chris; Petrou, Stavros; Botting, Beverley; Sutcliffe, Alastair G
Abstract : Objective: To determine the incidence of neonatal abstinence syndrome (NAS) across neonatal units, explore healthcare utilisation and estimate the direct cost to the NHS. Design: Population cohort study. Setting: NHS neonatal units, using data held in the National Neonatal Research Database. Participants: Infants born between 2012 and 2017, admitted to a neonatal unit in England, receiving a diagnosis of NAS (n=6411). Main outcome measures: Incidence, direct annual cost of care (£, 2016–2017 prices), duration of neonatal unit stay (discharge HR), predicted additional cost of care, and odds of receiving pharmacotherapy. Results: Of 524 334 infants admitted during the study period, 6411 had NAS. The incidence (1.6/1000 live births) increased between 2012 and 2017 (β=0.07, 95% CI (0 to 0.14)) accounting for 12/1000 admissions and 23/1000 cot days nationally. The direct cost of care was £62 646 661 over the study period. Almost half of infants received pharmacotherapy (n=2631; 49%) and their time-to-discharge was significantly longer (median 18.2 vs 5.1 days; adjusted HR (aHR) 0.16, 95% CI (0.15 to 0.17)). Time-to-discharge was longer for formula-fed infants (aHR 0.73 (0.66 to 0.81)) and those discharged to foster care (aHR 0.77 (0.72 to 0.82)). The greatest predictor of additional care costs was receipt of pharmacotherapy (additional mean adjusted cost of £8420 per infant). Conclusions: This population study highlights the substantial cot usage and economic costs of caring for infants with NAS on neonatal units. A shift in how healthcare systems provide routine care for NAS could benefit infants and families while alleviating the burden on services.